Energy-optimized versus cost-optimized design of high-performing dwellings: The case of multifamily buildings. (28th May 2018) - Ferrara, Maria; Sirombo, Elisa; Fabrizio, Enrico
Abstract : Living in multifamily buildings is very common in Italy, and it is important to optimize the design strategies to minimize the energy demand of these buildings and their related operational costs. This is particularly important for low-income tenants and is pursued by many social housing developments where a good energy performance design is reached. In this work, a simulation-based optimization methodology that combines the use of TRNSYS with GenOpt is applied to minimize two objective functions—the annual primary energy demand and the operational energy cost—in different system technology scenarios, and to verify the differences between energy-optimized design and cost-optimized design in a Northern Italy climate. The study is performed on a typical floor of a real multifamily building for social housing. The envelope optimization demonstrates a potential reduction of the energy demand and cost for heating and cooling of more than 35%. The relationship between optimal solutions, system technology scenarios, and optimization objectives is deeply analyzed. It is possible to find a set of design solutions that is optimal for all analyzed scenarios. This provides a set of design alternatives that is close to the environmental optimum and is able to reduce low-income tenants' vulnerability.